2007
DOI: 10.1080/00016350701771850
|View full text |Cite
|
Sign up to set email alerts
|

Digital images as an alternative to orthodontic casts in assessing malocclusion and orthodontic treatment need

Abstract: Two-dimensional digital images can be used as an alternative to casts in assessment of malocclusion and orthodontic treatment need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…need, 2-dimensional digital images can be used as an alternative to traditional orthodontic casts. 14 The use of digital models was found to be an accurate and reliable method for assessing patients' final occlusions. 15 In our study, age was found to be a significant factor affecting the amount of tooth movement: younger subjects (\16 years) showed significantly greater amounts of tooth displacement compared with older subjects (.16 years).…”
Section: Discussionmentioning
confidence: 99%
“…need, 2-dimensional digital images can be used as an alternative to traditional orthodontic casts. 14 The use of digital models was found to be an accurate and reliable method for assessing patients' final occlusions. 15 In our study, age was found to be a significant factor affecting the amount of tooth movement: younger subjects (\16 years) showed significantly greater amounts of tooth displacement compared with older subjects (.16 years).…”
Section: Discussionmentioning
confidence: 99%
“…According to Mok and coworkers, 23 two-dimensional digital photographs can be used alternatively to study casts in evaluating malocclusion and deciding whether orthodontic treatment is required.…”
Section: Discussionmentioning
confidence: 99%
“…However, calibrated examiners ensured high reliability of the IOTN grades from both oral examinations and plaster casts. 11,14,26,27 Appropriately, our examiners showed high intraexaminer reliability. However, we did not explicitly assess interexaminer variability here.…”
Section: Discussionmentioning
confidence: 94%